2022
DOI: 10.1111/iwj.13902
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of movement monitoring devices to aid the prediction of pressure ulcers in at‐risk adults

Abstract: The present study sought to explore the impact of movement monitoring devices on risk prediction and prevention of pressure ulcers (PU) among adults. Using systematic review methodology, we included original research studies using a prospective design, written in English, assessing adult patients' movement in bed, using a movement monitoring device. The search was conducted in March 2021, using PubMed, CINAHL, Scopus, Cochrane, and EMBASE databases, and returned 1537 records, of which 25 met the inclusion crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Moore and colleagues 47 recently updated their review (published after our search was conducted 79 ) and reported no new randomised trials that assessed the effect of risk assessment tools on PI incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Moore and colleagues 47 recently updated their review (published after our search was conducted 79 ) and reported no new randomised trials that assessed the effect of risk assessment tools on PI incidence.…”
Section: Discussionmentioning
confidence: 99%
“…16 The prevalence of PUs in various countries and medical settings has a wide range from 0% to 72.5%. 17 The incidence of PUs is 0.4%-38% in hospitals, 2.2%-23.9% in long-term care, and 0%-17% in home care. 18 The evidence states that having a positive attitude of nurses toward the prevention of PUs is one of the factors that have a favourable effect on preventive approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the publication of clinical practice guidelines for the prevention of PUs two decades ago, 15 the incidence rate of these injuries is still high, with 2.5 million people suffering from them annually only in the United States 16 . The prevalence of PUs in various countries and medical settings has a wide range from 0% to 72.5% 17 . The incidence of PUs is 0.4%–38% in hospitals, 2.2%–23.9% in long‐term care, and 0%–17% in home care 18 …”
Section: Introductionmentioning
confidence: 99%